Cancer Stem Cell Marker CD147 Expression in Erosive Oral Lichen Planus Compared to Moderately and Severely Dysplastic Leukoplakia - Vasileios Zisis; Nikolaos Nikitas Giannakopoulos; Athanasios Poulopoulos; Marc Schmitter; Dimitrios Andreadis (Reports, 2024)
Oral lichen planus is a frequent, chronic autoimmune disease that affects the oral mucosa and is characterized as an oral potentially malignant disorder. The aim of our study is to examine the presence of CSCs bearing CD147 (a marker related to local inflammation and associated with various cancers) through immunohistochemistry in oral lichen planus (OLP) compared to oral leukoplakia (OL) and healthy tissues. These findings could contribute to clinical practice by providing a marker for the prognostic assessment of OLP lesions with regards to their potentially malignant nature. The study sample consisted of paraffin-embedded oral mucosa specimens from the archives of the Department of Oral Medicine/Pathology, School of Dentistry, Aristotle University of Thessaloniki, Greece during the period 2009–2019. The study sample contained 24 cases of OLP (14 erosive and 10 reticular) and 30 cases of oral leukoplakia, which were compared to 5 normal oral epithelium samples derived from healthy epithelium adjacent to fibromas from other cases. Cell membrane staining of CD147 was observed mostly in the basal and parabasal cell layer. The statistically significantly higher expression of CD147 in the erosive lichen planus subgroup than in the moderately and severely dysplastic leukoplakia subgroup (p = 0.01) constituted the most important finding of this study. The characteristic expression of CD147 in erosive OLP suggests the presence of epithelial cells with CSC characteristics, but its lower expression in oral leukoplakias suggests a more intense relation of the CD147 marker with inflammation rather than with oral dysplastic progression.